Ртутный микрозонд для исследования локальных электрофизических свойств полупроводниковых структур - Popov, V. M.; Klimenko, A. S.; Pokanevich, A. P.; Shustov, Yu. M. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The construction of mercury microprobe has been proposed for measurement of electrophysical characteristics of semiconductor materials and IS(MIS) structures with 5—25 micron locality. Local electrophysical properties of technological Si–SiO2 structures with thin oxides in the region of electrically active defects on the silicon surface have been investigated. The influence of mechanical stresses near the edge of MIS structure electrodes on the local values of fixed charge in oxide has been shown.